Social Influencers as Catalysts for Digital Marketing Success: Engagement, Persuasion and Conversion - Polo, Dariene; Anino, Althea Rose; Matuseño, Paul Mark; Estrella, Carlo Ellis; Puno, Desiree; Rayses, Daniel; Domingo, Michael Darwin (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the influence of social influencers as catalysts for digital marketing success among selected respondents from the College of Business and Public Administration of Eulogio “Amang” Rodriguez Institute of Science and Technology (EARIST). Specifically, it assessed influencer attributes in terms of credibility and authenticity, attractiveness and personality appeal, content quality and consistency, audience interaction and responsiveness, and relevance to the target market. It also determined digital marketing success through engagement, persuasion, and conversion, identified challenges encountered in influencer marketing, and examined the relationship between influencer attributes and digital marketing success. A descriptive survey research design with a cross-sectional approach was employed. Data were collected through a validated survey questionnaire administered to 140 respondents, comprising 20 professors and 120 third-year Marketing Management students selected using purposive sampling. Weighted mean and percentage distribution were used to analyze the data. The findings revealed that respondents perceived social influencer attributes as effective across all measured dimensions and considered digital marketing success evident in terms of engagement, persuasion, and conversion. The study also identified personal, behavioral, strategic, and environmental challenges associated with influencer marketing. Furthermore, a significant relationship was found between social influencer attributes and digital marketing success, indicating that credibility, authenticity, content quality, audience interaction, and relevance positively influence consumer engagement, persuasion, and conversion. The study concludes that authentic communication, relevant and high-quality content, meaningful audience interaction, and transparency are essential to effective influencer marketing. It recommends maintaining influencer credibility, strengthening audience engagement, promoting digital literacy, and conducting further studies on additional factors influencing digital marketing success and the long-term effects of influencer marketing. The study aligns with Sustainable Development Goal (SDG) 8: Decent Work and Economic Growth and SDG 9: Industry, Innovation and Infrastructure, contributing to responsible digital marketing practices and innovation. Its findings also support socio-economic and digital sustainability by promoting consumer trust and effective marketing strategies.
Keywords: Audience Interaction; Content Quality; Digital Marketing; Engagement; Influencer Credibility; Social Influencers; Target Market; Transparency